Adaptación de dos Semillas de Maíz Forrajero (zea mays l.) en el Centro Experimental Académico Salache “CEASA” para su posterior suplementación en Cuyes de Engorde. - Benalcázar Aulestia, Lesly Gissela (2019)
Livestock production in Ecuador is based on rotating grazing, and pasture production is at the expense of climatic conditions (rainy season or drought). In the dry season, the yield and nutritional value of the forage biomass is limited, which reduces the productive performance of the animals.